The Value of 3.0-Tesla MRI in Diagnosing Scapholunate Ligament Injury - Spaans, Anne J.; Minnen, Paul van; Prins, Hendrik J.; Korteweg, Mies A.; Schuurman, Arnold H. (Journal of Wrist Surgery, 2013)
Objective To determine the sensitivity and specificity of 3.0-tesla (T) magnetic resonance imaging (MRI) and a dedicated hand coil in diagnosing scapholunate ligament (SLL) injury compared with intraoperative findings.Methods From January 2006 until September 2010, 3.0-T MRI scans were performed on 38 wrists (37 patients) with clinically unclear but suspected lesions of the SLL. These scans were evaluated by two experienced radiologists. Radiological findings were compared with intraoperative findings during arthrotomy. Sensitivity, specificity, accuracy, and positive and negative predictive value were calculated.Results An SLL lesion was identified during arthrotomy in 37 wrists. The first radiologist identified an SLL lesion on MRI in 26 wrists, all of which were confirmed intraoperatively. The second radiologist identified SLL lesions in 31 patients; however, intraoperatively it was found that there was no lesion of the ligament in one patient. Sensitivity ranged from 70 to 81% with a specificity of 100% and a positive predictive value of 97 to 100%. Accuracy measured 71 to 79%.Conclusions 3.0-T MRI of the wrist is moderately sensitive and very specific for detection of SLL lesions. However, if there is a high clinical suspicion of an SLL rupture, a 3.0-T MRI does not often have an additional value.Level of Evidence Diagnostic, level II
Keywords: 3.0 Tesla; magnetic resonance imaging; scapholunate ligament lesion; wrist arthrotomy